A real-time PCR assay for detection of light leaf spot on Brassica crops in the Pacific Northwest of the USA. Issue 4 (2nd October 2019) - Thomas, William J.; Serdani, Maryna; Claassen, Briana; Schneider, Morgan; Hinds-Cook, Althea M.; Mallory-Smith, Carol; Ocamb, Cynthia M.
Abstract: Outbreaks of light leaf spot ( Pyrenopeziza brassicae ), a disease new to North America, occurred along with the diseases blackleg ( Leptosphaeria spp.) and white leaf spot ( Mycosphaerella capsellae ) on Brassica crops in western Oregon. Disease symptoms in seed fields planted in the fall of 2013 were observed in the spring of 2014. Field surveys were conducted for disease during 2014 and 2015 to determine the geographic range of light leaf spot, blackleg, and white leaf spot within the Willamette Valley of western Oregon. Infected seed crops included turnip and oilseed rape in Benton, Lane, Linn, Marion, Polk, and Yamhill counties. New protocols that are more sensitive for detection of light leaf spot were developed for the pathogen population in the Pacific Northwest of the USA. Pyrenopeziza brassicae was detected when samples also contained L. maculans or M. capsellae . The test did not react with a range of other fungi evaluated. Sensitivity of the PCR protocol reported is robust at 10 pg of genomic DNA. Standard and real-time PCR screenings developed in this research increase sensitivity for detection of P. brassicae in affected Brassica hosts, which is critical for timely diagnosis and management of this newly-introduced disease in Brassica crops in the Pacific Northwestern region of the USA.